Efeito residual do calcário e da escória de siderurgia em soqueiras da cana-de-açúcar - Almeida, Thiago Batista Firmato de [UNESP] (2015)
Proper management of soil fertility with the use of corrective materials with higher residual effect may reflect production and longevity of sugarcane crop. This study aimed was to evaluate the residual effect of limestone and slag as soil amendments material and source of Si in ratoon sugarcane, monitoring the potentially toxic metals (Cd, Cr, Ni and Pb) in soil and plant in without straw removal by burning harvesting system, grown in an Oxisol. The study was conducted in FCAV/UNESP-Campus of Jaboticabal, with RB855156 variety in the 2010/2011 and 2011/2012. The experimental design was randomized blocks, in 2x4 factorial design, with the two amender in four rates (ECaCO3 = 0, 0.9, 1.8 and 3.6 t ha-1), with four replications, totaling 32 experimental units. Soil samples were taken at 30 and 36 months and 42 months and 48 months after amendment materials applications, by collecting 10 points per plot, at 0-10; 10-20; 20-40 and 40-60 cm depth, determining the chemical soil fertility analysis, silicon content (Si) and of potentially toxic metals (Cd, Cr, Ni and Pb). Was held the leaf analysis and were determined the Si content and heavy metals in the leaves. For growth analysis the number of tillers at 120 days after sprouting, and the number of stems to 270 and 390 days after sprouting, 1.5 m row were considered. The height was measured from the base of the stem to the insertion of the sheet +1 (TVD: Top Visible Dewlap) and the average diameter of the stem base were measured at 8 cm above the soil surface, 10 plants per working area. It was determined the mass of dry matter of stems and technological quality. The residual effect of limestone and slag showed similar effects on soil chemical properties at 30 months and slag showed at 36 months a better performance than the limestone in some attributes (pH, V% and Si). After 42 months the ...